Development of Digital Teaching Materials through Instagram Social Media as an Alternative Media for Learning Français du Tourisme - Yamin, Denisa Nur Ramadhanti; Indri Hardini, Tri; Sopiawati, Iis; Brebion, Yaëlle (Unit Bahasa, Politeknik Pariwisata NHI Bandung, 2023)
Learning French for tourism purposes Français du Tourisme plays an important role in preparing students to face global challenges in the growing tourism industry. In this digital era, the use of social media as a learning tool has become a trend that promises to provide innovative and interesting learning experiences. One of the popular social media is Instagram, which provides various creative features to support the development of digital teaching materials. This research aims to develop innovative and interesting digital teaching materials for learning Français du Tourisme through Instagram social media. The research method used is development research with planning, production, and evaluation stages. Data collection was carried out through surveys and interviews to find out the needs and preferences of students, as well as their responses to the teaching materials developed. The results of the study show that Instagram social media can be an effective alternative medium for learning French tourism. Digital teaching materials developed through Instagram are able to provide fun and innovative learning experiences, thus increasing student motivation and participation in the learning process. Creative features on Instagram, such as posting pictures, videos, stories, and slide shows can be utilized optimally to present materials relevant to the tourism context. In conclusion, the development of digital teaching materials through social media Instagram is a positive step in enriching the learning experience of Français du Tourisme. However, there needs to be a balanced approach between the use of technology and effective learning strategies. This research contributes to the field of social media-based curriculum development in the context of learning French for tourism, and can be a reference for teachers and practitioners in the fields of language education and tourism.